2018
DOI: 10.1519/jsc.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Midthigh Pull Reliability and Relationship to Deadlift One Repetition Maximum

Abstract: De Witt, JK, English, KL, Crowell, JB, Kalogera, KL, Guilliams, ME, Nieschwitz, BE, Hanson, AM, and Ploutz-Snyder, LL. Isometric midthigh pull reliability and relationship to deadlift one repetition maximum. J Strength Cond Res 32(2): 528-533, 2018-The purpose of this investigation was to examine the reliability of the isometric midthigh pull (IMTP) and the relationship between IMTP peak force and deadlift 1 repetition maximum (1RM). Nine subjects (5 men and 4 women; 40.6 ± 8.0 years; 1.72 ± 0.10 m; 75.6 ± 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 15 publications
9
67
2
Order By: Relevance
“…Therefore, coaches and researchers are advised to specify and standardise their knee and hip joint angles adopted for IMTP testing and state whether absolute or relative joint angles were measured to avoid confusion and allow the replication of IMTP testing methodologies. **Insert Figure 2 about here** The present study found PF to demonstrate the highest between-session reliability measures for both postures (Table 2) similar to the observations of previous between-session (ICC ≥ 0.89 , CV ≤ 4.6%) (8,11,15,45) and within-session research (ICC ≥ 0.97 , CV ≤ 3.2%) (12,22). Equally, both postures demonstrated high levels of within-session reliability for timespecific force values (Table 1) comparable to the reliability measures reported in previous research (4,12,22,29).…”
Section: A C C E P T E Dsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, coaches and researchers are advised to specify and standardise their knee and hip joint angles adopted for IMTP testing and state whether absolute or relative joint angles were measured to avoid confusion and allow the replication of IMTP testing methodologies. **Insert Figure 2 about here** The present study found PF to demonstrate the highest between-session reliability measures for both postures (Table 2) similar to the observations of previous between-session (ICC ≥ 0.89 , CV ≤ 4.6%) (8,11,15,45) and within-session research (ICC ≥ 0.97 , CV ≤ 3.2%) (12,22). Equally, both postures demonstrated high levels of within-session reliability for timespecific force values (Table 1) comparable to the reliability measures reported in previous research (4,12,22,29).…”
Section: A C C E P T E Dsupporting
confidence: 86%
“…The IMTP is commonly used to assess the peak force (PF) production but a further advantage is the ability to inspect an athlete's ability to produce force (4,12,15,22), rate of force development (RFD) (4,12,22) and impulse (8,43) at critical time intervals. The IMTP has been shown to demonstrate high within-and between-session reliability measures for PF (8,11,14,15,22), time-specific force values (4,12,15,22), rate of force development (12,22) and impulse (8,43) across different time intervals. Due to the high reliability and its simplicity to administer, the IMTP is commonly used to evaluate the force-time qualities to prescribe future training such as inspection of the dynamic strength index when combined with PF during a jump (45); while also used to monitor adaptations to training (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometric mid-thigh pull (IMTP) was assessed using a customised testing rig, consisting of two Pasco force plates (Roseville, California) and perpendicular vertical poles drilled at 1 cm increments to allow appropriate grip adjustment and positioning of the bar to the participants' mid-thigh. Intraclass correlation coefficient (ICC) statistics in similar protocols have shown reliable measures both within (ICC = 0.97) and between (ICC = 0.89) sessions [23]. A demonstration of the IMTP was provided by the researcher prior to the first trial, and participants had an opportunity to practise the hand grip placement and pulling position prior to commencement.…”
Section: Methodsmentioning
confidence: 99%
“…Isometric multi-joint tests are a common method of assessing maximal force capacity. There are numerous lines of enquiry that have used squat [4][5][6][7] and mid-thigh pull [8][9][10] exercises.…”
Section: Introductionmentioning
confidence: 99%